Preliminary protocol development of a hplc-tbars-evsc (Ex vivo stratum corneum) assay for skin research: Application in a sunscreen system - Sauce, Rafael (2021)
This research was funded by Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP), grant numbers 2016/24360-4 and 2019/16169-0; Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq), process 305250/2019-1; CONCYTEC-FONDECYT, process E041-01 (Contract number 123-2018-FONDECYT-BM-IADT/AV); and Coordenação de Aperfeiçoamento de Pessoal de Nível Superior-Brasil (CAPES) Finance Code 001.